The ambiguity of trust in Higher Education - Kelland, Lindsay (Critical Studies in Teaching and Learning, 2025)
A key assumption made in the literature is that trust in education is positive. This assumption underpins the work of notable scholars of education, such as Freire (1970) and hooks (1994), and is reiterated in Magadla’s (2023) remarks in ‘Trust as a condition for radical entanglement’. While I agree with them that it is essential for trust to exist in a healthy and humanising learning environment, I am also mindful of calls for caution, such as those offered by Rice (2006) and Kovač and Kristiansen (2010), which provide reasons to believe that excessive trust can have negative effects on learning and the environments and relationships within which learning takes place. Given calls for and against the promotion of trust in education spaces and drawing on my experiences co-creating and co-facilitating a student-led and student-centred course in ethics, I suggest the need to recognise the ambiguity of trust in higher education.